2017
DOI: 10.1007/s10570-017-1582-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment of cellulose nanocrystals (CNC): effects on dispersion rheology

Abstract: Cellulose nanocrystals (CNC) were surface modified by grafting azetidinium salts onto the sulphate ester groups on the cellulosic surfaces. The modified CNC were characterized using NMR, FTIR spectroscopy, conductometric titration and measurement of the f-potential. Thermal gravimetrical analysis revealed that the onset temperature for the thermal degradation was shifted upwards by almost 100°C as a result of the surface grafting. The rheological properties of dispersions based on unmodified and modified CNC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 40 publications
4
48
0
Order By: Relevance
“…Suspensions of cellulose nanocrystals were prepared by acid hydrolysis of a commercially available microcrystalline cellulose (Avicel Ò PH-101) using a procedure described in an earlier publication (Sahlin et al 2017) adapted from Hasani et al (2008). Hydrolysis of 500 g microcrystalline cellulose was performed using 4.37 dm 3 of 64% w/w sulphuric acid at 45°C for 2 h under continuous stirring, after which the suspension was diluted with deionised water to quench the reaction.…”
Section: Preparation Of the Cellulose Nanocrystalsmentioning
confidence: 99%
“…Suspensions of cellulose nanocrystals were prepared by acid hydrolysis of a commercially available microcrystalline cellulose (Avicel Ò PH-101) using a procedure described in an earlier publication (Sahlin et al 2017) adapted from Hasani et al (2008). Hydrolysis of 500 g microcrystalline cellulose was performed using 4.37 dm 3 of 64% w/w sulphuric acid at 45°C for 2 h under continuous stirring, after which the suspension was diluted with deionised water to quench the reaction.…”
Section: Preparation Of the Cellulose Nanocrystalsmentioning
confidence: 99%
“…However, the presence of acid sulphate groups reduces the thermal stability of the nanocellulose, and thermal degradation, which has been attributed to a dehydration reaction [21,22], may commence already at 150°C. In an earlier work [23], it was shown that the onset of thermal degradation of CNC obtained through sulphuric acid hydrolysis could be delayed by almost 100°C by grafting azetidinium salts onto the sulphate ester groups on the CNC surface. Sahlin et al [23] used three different chemical groups to modify the CNC; N-morpholino-3-methoxyazetidinium, N,N-dihexyl-3-methoxyazetidinium and N,N-diallyl-3methoxyazetidinium.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier work [23], it was shown that the onset of thermal degradation of CNC obtained through sulphuric acid hydrolysis could be delayed by almost 100°C by grafting azetidinium salts onto the sulphate ester groups on the CNC surface. Sahlin et al [23] used three different chemical groups to modify the CNC; N-morpholino-3-methoxyazetidinium, N,N-dihexyl-3-methoxyazetidinium and N,N-diallyl-3methoxyazetidinium. In addition to the improvement in thermal stability, the surface modifications of the CNC resulted in a significant increase in the shear viscosity at a given shear rate and in the dynamic moduli of aqueous dispersions containing 0.65 and 1.3 wt% CNC, and there was a corresponding decrease in the concentration at which gel formation took place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of this biomaterial is the capacity of CNCs to be easily modified chemically. Surface functionalization of CNCs aims to improve surface properties and has been intensively investigated due to the reactive surface of —OH side groups that facilitate grafting chemicals species, for example, 3‐aminopropyltriethoxysilane, to achieve enhanced thermal stability, triazinyl derivatives, resulting in stable colloidal suspensions of CNCs in polar and non‐polar organic solvents, azetidinium salts, to improve the rheological properties of CNCs, polylactide, to improve barrier properties, or genetically engineered peptides (elastin like‐polypeptides) with temperature responsiveness to produce multifunctional biopolymers . It is worth noting the chemical alteration made by Hu et al, which have proposed and environmentally friendly procedure for the surface modification of CNC with tannic acid (TA), a plant polyphenol, acting as an intermediary for the Michael‐type addition covalent of decylamine (DA), an hydrophobe group.…”
Section: Physicochemical Characterization Of Cellulose Nanocrystalsmentioning
confidence: 99%